STUDI RAGAM PENGOLAHAN PASCA PANEN BIJI KOPI TERHADAP KEUNTUNGAN, KEPUASAN DAN LOYALITAS KONSUMEN KOPI GHALKOFF - Siti Ghalika Permata Suri Almega; Yaktiworo Indriani; Adia Nugraha (Lampung University, 2022)
Lampung Province has a great potential yield of coffee plantations. This potential causes the rise of coffee-based businesses. PT. Ghaly Roelies Indonesia is one of the coffee-based agro-industry in Lampung Province. This research aims to analyze the benefits of Ghalkoff Coffee’s products as well as consumers' satisfaction and loyalty on Ghalkoff Coffee beverages based on the variety of processing. This research was conducted in two places, namely PT. Ghaly Roelies Indonesia’s agro-industry and Ghalkoff Cafe. The research was conducted by using survey method, involving 58 respondents, in which data were collected by conducting interviews based on the consumers’ purchase histories. The data were analyzed by Cost of Sales, Customer Satisfaction Index (CSI), and Loyalty Pyramid analysis. The analysis showed that the variety of processing affected the profits, which was shown by profits of 50.67 to 66.51%. The highest profit was obtained by the coffee processing of F12 variant which was about IDR 365,794.28/kg. The lowest profit was obtained by the coffee processing of F2 variant which was about IDR 91,205.58/kg. The level of customer satisfaction on consuming Ghalkoff Coffee beverages was on the criteria of being very satisfied with the CSI value of 85.66%. Ghalkoff Coffee beverage consumer loyalty was at Liking the Brand level with value of 87.93% based on loyalty pyramid analysis test. Key words : Consumers, loyalty, processing, profits, satisfied.